Analysis of fluoroquinolone-resistance using MIC determination and homology modelling of ParC of contemporary Mycoplasma genitalium strains. Issue 3 (March 2022) - Hamasuna, Ryoichi; Hanzawa, Hiroyuki; Moritomo, Ayako; Matsumoto, Masahiro; Aono, Hisami; Tomisaki, Ikko; Akasaka, Takaaki; Fujimoto, Naohiro; Jensen, Jørgen Skov
Abstract: Introduction: The mechanisms of fluoroquinolone-resistance of Mycoplasma genitalium were analysed by a new method. Methods: M. genitalium strains from urinary sediments of patients with urethritis were isolated and examined antimicrobial susceptibilities and the mutations in ParC, GyrA and 23S rRNA. Docking models between gyrase and topoisomerase IV with sitafloxacin showed that two binding modes in which the amine moiety at the C-7 position rotated could be constructed. Results: Among 18 strains, 13 strains had mutations with amino-acid changes at Serine 83 in ParC. The MICs of moxifloxacin or sitafloxacin for three strains with only S83I in ParC were 2, 1 and 8 mg/L (moxifloxacin) or 0.13, 0.13 and 1 mg/L (sitafloxacin), respectively. In contrast, the MICs of moxifloxacin or sitafloxacin for 3 strain with S83N in ParC were 0.25, 0.13 and 0.25 mg/L (moxifloxacin) or 0.06, 0.03, and 0, 03 mg/L (sitafloxacin), respectively, not significantly different from wild-type isolates. The docking model of sitafloxacin and topoisomerase IV showed that the oxygen atom at the gamma position of Serine 83 of ParC interacted with the sitafloxacin carboxylate moiety. When the S83I substitution occurs, the isoleucine side chain is lipophilic and the residue hydropathy changes from hydrophilicity to hydrophobicity and important H-bond interactions between serine and the carboxylate moiety are lost. When the serine 83 to asparagine substitution (S83N) occurred, the asparagine side chain is hydrophilic and the residue hydropathy does not change. Conclusion: The docking model suggests that Ser83 replacements causes attenuation or loss of activity of fluoroquinolones such as sitafloxacin.